Comparative machinability study of ADI-4h and mild steel using WEDM. (14th March 2023) - Sarma, Pranjal; Borah, Dibya Jyoti; Patowari, Promod Kumar; Likhite, Ajay
Austempered ductile iron (ADI) has been gaining increasing popularity due to its interesting mechanical properties. But its machining by conventional methods is difficult. We report the machining processing response of ADI-4h while processing under wire electric discharge machining (WEDM). The effect of the major WEDM process parameters viz. peak current, pulse-on-time and wire feed on the major response parameters viz. cutting rate, kerf width and surface roughness has been investigated. A comparative machinability study is also carried out with mild steel. Study reveals that ADI shows fairly good machinability under WEDM even though mild steel is more easily machinable. SEM analysis reveals presence of nodular graphite and ausferritic microstructure on the matrix of synthesised ADI-4h and an average recast layer thickness of 6 µm after WEDM processing. The study can help researcher and industries to better understand ADI machinability via WEDM and hence augment its application in various fields.